2016
DOI: 10.1186/s12936-016-1240-7
|View full text |Cite
|
Sign up to set email alerts
|

Parasite clearance rates in Upper Myanmar indicate a distinctive artemisinin resistance phenotype: a therapeutic efficacy study

Abstract: BackgroundArtemisinin resistance in Plasmodium falciparum extends across Southeast Asia where it is associated with worsening partner drug resistance and a decline in the efficacy of frontline artemisinin-based combination therapy. Dihydroartemisinin-piperaquine (DP) is an essential component of preventive and curative treatment in the region, but its therapeutic efficacy has fallen in Cambodia.MethodsA prospective clinical and parasitological evaluation of DP was conducted at two sites in Upper Myanmar betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 37 publications
1
56
2
Order By: Relevance
“…The study realized in Myanmar indicated median parasite half-life was prolonged and clearance half-life was also greater than 5 h in 21% of enrolled patients. There were a significant association between delayed parasite clearance and polymorphisms in propeller kelch 13 region of P. falciparum (Tun et al, 2016).…”
Section: Studies Assessing Delayed Parasite Clearance Time As Marker mentioning
confidence: 99%
See 2 more Smart Citations
“…The study realized in Myanmar indicated median parasite half-life was prolonged and clearance half-life was also greater than 5 h in 21% of enrolled patients. There were a significant association between delayed parasite clearance and polymorphisms in propeller kelch 13 region of P. falciparum (Tun et al, 2016).…”
Section: Studies Assessing Delayed Parasite Clearance Time As Marker mentioning
confidence: 99%
“…This in vivo phenotype was not coupled with any in vitro resistance phenotype as per the standard in vitro susceptibility testing (Ashley et al, 2014;Dondorp et al, 2012;Takala-Harrison et al, 2014;Thriemer et al, 2014;Tun et al, 2016).…”
Section: Delayed Parasite Clearance Time As Marker Of Artemisininresimentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, ASMQ efficacy in 5 Cambodian provinces where DP was failing in 2014-2016 was 100% at day 42 (n = 305), even though 94.2% (278/295) of parasites carried the K13 C580Y mutation (Amaratunga et al, unpublished data; Rithea et al, unpublished data). High ACT efficacy despite high K13 mutation prevalence has also been reported in neighboring countries [4][5][6][7].…”
mentioning
confidence: 97%
“…To this end, the World Health Organization has supported the development of a malaria elimination strategy for this region, and is currently integrating it into the national malaria control programs of all GMS countries [9]. Charlotte Rasmussen, 1 Frédéric Ariey, 2 Rick M. Fairhurst, 3 Pascal Ringwald, 1 and Didier Ménard 4,5,6 …”
mentioning
confidence: 99%